The relationship between Yahweh and Israel as expressed by certain metaphors and similes in the Book of Hosea - Krüger, P. A. (Paul Albertus), 1948- (Stellenbosch : Stellenbosch University, 2012)
Thesis (DLitt)--Stellenbosch University, 1983.